Sustainability Index of Rice Field for Supporting Spatial Planning (Case Study in Jember District, East Java) - . NURWADJEDI; BUDI MULYANTO; SUPIANDI SABIHAM; ARIS PONIMAN; . SUWARDI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
Rice Field agriculture in Jember district is a main sector due to its contribution to rice production in this region. The objective of this study is to determine the rice field sustainability index based on agro-ecosystem zone and to formulate policy alternatives for supporting the spatial planning in achieving sustainable rice field agriculture. The study used the primary andsecondary data which include biophysical environment, economy, social and culture. The data analysis used GIS (Geographic Information System) modelbase, factor analysis, and AHP (Analytical Hierarchy Process). The results showed that the sustainability index of the rice field agro-ecosystem zones were different. The threats of the rice field sustainability were causedby the main indicators of the biophysical environment, economy, social, and culture such as water availability, soil nutrients of Carbon organic content, Nitrogen, and Phosphor-available, profit, fertilizer access, land conversion, land ownership and fragmentation, farmer education, and age of farmer. To overcome those threats, the policy consideration was more dominantly determined by the biophysical factor rather than that of theeconomy, social, and culture. The implementation of the policy tohandle the threats needs to be coordinated among the stakeholders, considering that the rice field resource can be categorized into a common pool resource.